In silico development of a multi-epitope-based vaccine against Burkholderia cepacia complex using reverse vaccinology - Ghorbani, Donya; Beig, Masoumeh; Noori Goodarzi, Narjes; Sholeh, Mohammad; Shahbazi, Behzad; Moghaddam, Yaser; Badmasti, Farzad (Frontiers in Virology, 2025)
BackgroundMultidrug-resistant Burkholderia cenocepacia and Burkholderia multivorans have emerged as significant pathogens, particularly in patients with cystic fibrosis (CF) and chronic granulomatous disease (CGD).ObjectiveGiven the absence of approved vaccines, this study aimed to identify potential vaccine candidates against these pathogens.MethodsThe complete genomes of B. cenocepacia and B. multivorans were retrieved from the GenBank. Surface-exposed proteins that were antigenic, non-allergenic, and non-homologous to human proteins were selected for further analysis. The conserved domains of the selected proteins were analyzed, and their presence was examined across 68 genomes. Subsequently, linear and conformational B-cell epitopes and human MHC II binding sites were identified. Highly conserved and immunogenic B-cell epitopes from outer membrane proteins (OMPs) were incorporated into a multi-epitope vaccine (MEV). Molecular docking analysis was performed to assess the interaction of the selected proteins. Finally, molecular dynamics (MD) simulations were conducted using GROMACS 2019 to evaluate the feasibility and dynamics of the interactions between the chimeric MEV and Toll-like receptor complexes, TLR2 and TLR4.ResultsOf 16,723 proteins identified in B. multivorans and B. cenocepacia strains, nine proteins (six OMPs and three extracellular) were selected as ideal candidates based on established criteria. These proteins had a molecular weight of 110 kDa and were present in ≥ 75% of the dataset of B. multivorans and B. cenocepacia genomes. In addition, molecular docking and MD indicated stable and feasible interactions between MEV and TLRs. The MEV-TLR4 system demonstrates the greatest stability and tightly bound interaction, with minimal fluctuations and high structural integrity. In contrast, the MEV-only system exhibits significant flexibility and dynamic behavior as a free ligand, while the MEV-TLR2 system balances stability and flexibility, showing a dynamic but stable interaction.ConclusionNine potential immunogenic proteins were identified as viable targets for vaccine development. An optimized MEV was explicitly designed for B. multivorans and B. cenocepacia. The novel MEV platform exhibited high binding affinity to immune receptors and favorable molecular docking characteristics. Although these findings are encouraging, additional in vitro and in vivo testing is necessary to validate the vaccine’s effects.